2018
DOI: 10.1186/s13073-018-0569-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional and genomic analyses reveal therapeutic potential of targeting β-catenin/CBP activity in head and neck cancer

Abstract: BackgroundHead and neck squamous cell carcinoma (HNSCC) is an aggressive malignancy characterized by tumor heterogeneity, locoregional metastases, and resistance to existing treatments. Although a number of genomic and molecular alterations associated with HNSCC have been identified, they have had limited impact on the clinical management of this disease. To date, few targeted therapies are available for HNSCC, and only a small fraction of patients have benefited from these treatments. A frequent feature of HN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Various mechanisms may contribute to activation of Wnt signaling in HNSCC, thus, potentially both upstream and downstream proteins may serve as suitable targets for downregulation of this cascade. In order to assess pathway inhibition, expression levels of Axin2, MMP7, BIRC5 as well as c-MYC and CCND1, were used as pharmacodynamic readouts, similar to other recent studies [24,[32][33][34]. Interestingly, cell membrane-bound Porcupine and nuclear CBP emerged as the best targets for the effective down-regulation of Wntdependent gene expression in the HNSCC cells tested.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Various mechanisms may contribute to activation of Wnt signaling in HNSCC, thus, potentially both upstream and downstream proteins may serve as suitable targets for downregulation of this cascade. In order to assess pathway inhibition, expression levels of Axin2, MMP7, BIRC5 as well as c-MYC and CCND1, were used as pharmacodynamic readouts, similar to other recent studies [24,[32][33][34]. Interestingly, cell membrane-bound Porcupine and nuclear CBP emerged as the best targets for the effective down-regulation of Wntdependent gene expression in the HNSCC cells tested.…”
Section: Discussionmentioning
confidence: 96%
“…PRI-724 is a second generation antagonist of CBP/βcatenin interaction, which has already entered clinical trials [33]. It is a more potent enantiomer of ICG-001, which has been shown to reduce the growth of head and neck cancers in preclinical experiments [34,36,37]. In our study, PRI-724 reduced the level of expression of β-catenindependent genes, but it had a weaker effect on the production of TCF/LEF reporter-based luciferase than IWP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its inhibition with ICG-001 led to significant anti-cancer effects-it reduced the growth of oral tumors and inhibited metastasis in vivo. Moreover, detailed analyses have shown that this compound selectively targeted cancer stem-like cell subpopulations [130,131]. Canonical Wnt signaling was shown to be necessary for the induction of pluripotency by the creation of permissive chromatin in stemness gene promoters.…”
Section: Functional Significance Of Wnt/β-catenin Pathway Dysregulationmentioning
confidence: 99%
“…reduced stemness [102] decreased cell invasion [106] cell cycle arrest, reduced cell migration, induction of apoptosis [51,107] decreased cisplatin resistance [102] increased radiosensitivity [135] Porcupine IWP-2 inhibitor inhibition of UCA1dependent Wnt activation reduced cell proliferation and migration [84] LGK974 inhibitor reduced Wnt target gene expression reduced tumor growth [125] C59 inhibitor reduced secretion of WNT-3A, reduced CCND1 and BIRC5 expression impaired HPV-driven transformation [126] CBP ICG-001 inhibitor altered gene expression cell cycle arrest, induction of apoptosis, reduced stemness, tumor growth and metastasis [130,131] PI3K pathway emodin inhibition of PI3K/Akt/ β-catenin pathway reduced cell invasiveness [111] pyrithione zinc reduced expression of CCND1 and c-MYC reduced cell proliferation and invasion, apoptosis [119] CUL4B knockdown reduced expression of CCND1, c-MYC, MMP-7 reduced cell growth, migration and invasion [113] Funding: This work was funded by the Polish National Science Centre, grant number 2014/13/D/NZ7/00300.…”
Section: Lef1mentioning
confidence: 99%
“…32 Moreover, ICG-001 effectively suppressed tumour metastasis of aggressive subpopulations of oral squamous cell carcinoma stem-like cells in zebrafish embryos. 33 By disrupting Wnt signalling, ICG-001 also exerts potent effects against leukaemia stem cells. 34 Using clinical databases and patient tumour samples, dual inhibition of Wnt and YAP using ICG-001 and simvastatin, respectively, powerfully suppressed CSC populations in triple negative breast cancer (TNBC).…”
Section: Icg-001(pri 724)mentioning
confidence: 99%